Closed-Circuit Television (CCTV) Sebagai Pengawasan Digital di Lorong Wisata Kota Makassar - Juniarsi Nur, Andi Ainun; Gunawan, Wahyu; Sugandi, Yogi Suprayogi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The rapid advancement of surveillance technology, particularly the adoption of Closed-Circuit Television (CCTV), has revolutionized public safety measures. In Makassar City's Lorong Wisata, CCTV serves as a critical tool for monitoring public spaces, reducing crime, and enhancing the sense of security. This study aims to explore the effectiveness and challenges of CCTV implementation as a digital surveillance mechanism. Using a qualitative descriptive approach, data were collected through in-depth interviews and observations involving local government officials, law enforcement, and community members, analyzed with NVivo 14 software. Results indicate that CCTV has significantly improved public safety by deterring crime and facilitating law enforcement investigations. However, concerns about privacy infringement and the psychological "chilling effect" are prominent, as constant surveillance influences community behavior and limits personal freedom. Furthermore, the potential misuse of collected data raises additional privacy concerns. This study emphasizes the importance of transparent regulations, active community engagement, and periodic evaluations to balance public safety and individual privacy. Holistic approaches integrating technology with social reform are necessary to ensure effective and ethical surveillance practices.